ESTUDIO DE LA SEGURIDAD DE LA RED DE DATOS DEL GAD FEBRES CORDERO - Campi Martinez, Mauricio Fernando (2018)
The GADP (Autonomous Decentralized Parish Government) of Febres Cordero of the Province of Los Ríos, Babahoyo canton, is an institution with the purpose of leading, articulating processes of development in the parish, promotes and executes Public Policies in order to solve the needs of all the inhabitants of the Parish. Autonomous Decentralized Parish Government of Febres Cordero, has as mission to achieve a high human development reducing environmental pollution, conserving existing ecosystems diversifying and implementing a sustainable economy, generating well-being for a good life in all families, population of the Parish Febres Cordero incentivando , values ​​and principles. The present case study will analyze the security flaws in the data network of the institution, in this data system consists of connectors, channels and devices, which allows establishing a communication system in a telecommunications infrastructure within the building. In a secure data network, always keep in mind the characteristics and standards that must be met. The Data Network allows to transport inside the building the information and signals that are sent from the issuer and received by the recipient (s). In the physical network you can easily change the UTP cables, connection blocks, adapters among other elements of the wiring structure. By supporting different telecommunications devices, without having the greatest knowledge about the products that are used on it.